A Prospective Observational Study on Evaluation of Chemotherapy Induced Adverse Drug Reactions in Cancer Patients in a Tertiary Care Hospital - Koliyakodu, Priya Saji; Sudhakar, Rona; Kurian, Manesh Mathews; R. K, Jishnu; Kumar, Raj; Lalitha, V.; Sherief, Haja; Sivakumar, T. (Journal of Pharmacy Practice and Community Medicine)
Aim: To analyze the incidence of adverse drug reactions due to chemotherapy by studying the prescribing patterns and thereby evaluating their causality and severity. Materials and Methods: It was a prospective observational study conducted for a period of 6 months, from February 2018-July 2018 in a tertiary care hospital. The specifics were collected based on the inclusion and exclusion criteria from the Oncology department. The reported ADRs were assessed for causality using both WHO and Naranjo’s algorithm and severity were assessed using Modified Hartwig and Siegel scale. Results: It was observed that 852 ADRs were reported from 250 patients. Most common age group in which patient had ADRs were 46-60 years (39.2%) followed by age group above 60 years (35.2%). Cervix cancer was the most commonly distributed (23.2%) followed by breast cancer (13.6%). The prescribing pattern of combination therapy (83.6%) was more compared to monotherapy (16.4%). Cisplatin and cisplatin–paclitaxel regimen induced more ADRs in monotherapy and combination therapy respectively. WHO causality scale indicated 68.4% of the reactions were “probable” and 25.6% were “possible”. Modified Hartwig and Siegel scale indicated that 71.2% were moderate followed by mild 24.8% and 4% were severe. Conclusion: Treatments like chemotherapy makes the disease real. Benefits of treatment should outweigh the risk. We assessed the incidence of ADRs, analyzed the prescribing patterns categorized the causality and severity and notified the suspected ADRs in order to promote the judicious use of suspected drugs with regular and sustained monitoring. This knowledge helps in preventing the occurrence of similar reactions in future.
Keywords: Cancer; Adverse Drug Reactions; Chemotherapy; Monotherapy; Combination therapy.